2002
DOI: 10.5012/bkcs.2002.23.6.865
|View full text |Cite
|
Sign up to set email alerts
|

The Orientation of CO in Heme Proteins Determined by Time-Resolved Mid-IR Spectroscopy: Anisotropy Correction for Finite Photolysis of an Optically Thick Sample

Abstract: A systematic way of determining the equilibrium orientation of carbon monoxide (CO) in heme proteins using time-resolved polarized mid-IR spectroscopy is presented. The polarization anisotropy at pump-probe delay time of zero in the limit of zero photolysis and the angular distribution function of CO are required to obtain the equilibrium orientation of CO. An approach is developed for determining the polarization anisotropy in the zero-photolysis limit from the anisotropy measured under finite photolysis cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Under our experimental conditions using a sample near the optically thin limit and <10% excitation energy, the deviation is estimated <∼3% (cf. ref ); hence substantially smaller than the variation in anisotropy used to discuss the results (see below).…”
Section: Resultsmentioning
confidence: 92%
“…Under our experimental conditions using a sample near the optically thin limit and <10% excitation energy, the deviation is estimated <∼3% (cf. ref ); hence substantially smaller than the variation in anisotropy used to discuss the results (see below).…”
Section: Resultsmentioning
confidence: 92%
“…Due to the excellent short-term stability of the IR light source (<0.5% rms), the noise is less than 1 × 10 -4 rms in absorbance units after 0.5 s of signal averaging without single shot referencing with an independent detector. The pump spot (180 μm diameter) was made larger than the probe spot (120 μm diameter) to ensure spatially uniform photoexcitation across the spatial dimensions of the probe pulse . Moderate pump energy with an enlarged photolysis beam size also minimizes spatial thermal effects.…”
Section: Methodsmentioning
confidence: 99%
“…Recent advances in time-resolved IR spectroscopy make it possible to probe subtle changes in absorbance on femtosecond time scales, enabling us to directly probe GR dynamics of MbNO in aqueous solution at room temperature. Here, we report the use of femtosecond IR spectroscopy in probing GR dynamics of NO after photolysis of MbNO and MpNO in aqueous solution at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the appropriate correction factor for an optically thick sample can be calculated as a sum over optically thin ones, with parameters in each optically thin slice determined according to the fraction of molecules photolyzed within that slice, i.e where i is the index for each slice and f i is its fractional contribution to the total number of photolyzed molecules …”
Section: Relations Between Co Orientation and Polarization Anisotropymentioning
confidence: 99%
“…It should be noted that if the photolysis pulse is sufficiently short in duration, A * corresponds to the excited-state absorbance of the sample, not the ground-state absorbance of the photoproduct. The correction factor becomes a strong function of A and A * at higher levels of photolysis, thereby causing the optically thick correction factor to differ significantly from the optically thin limit ( A → 0) …”
Section: Relations Between Co Orientation and Polarization Anisotropymentioning
confidence: 99%